Plasmablast Expansion Following the Tetravalent, Live-Attenuated Dengue Vaccine Butantan-DV in DENV-Naïve and DENV-Exposed Individuals in a Brazilian Cohort - Silveira, Cássia G. T.; Magnani, Diogo M.; Costa, Priscilla R.; Avelino-Silva, Vivian I.; Ricciardi, Michael J.; Timenetsky, Maria do Carmo S. T.; Goulart, Raphaella; Correia, Carolina A.; Marmorato, Mariana P.; Ferrari, Lilian; Nakagawa, Zelinda B.; Tomiyama, Claudia; et al. (Frontiers in Immunology, 2022)
An effective vaccine against the dengue virus (DENV) should induce a balanced, long-lasting antibody (Ab) response against all four viral serotypes. The burst of plasmablasts in the peripheral blood after vaccination may reflect enriched vaccine-specific Ab secreting cells. Here we characterize the acute plasmablast responses from naïve and DENV-exposed individuals following immunization with the live attenuated tetravalent (LAT) Butantan DENV vaccine (Butantan-DV). The frequency of circulating plasmablasts was determined by flow cytometric analysis of fresh whole blood specimens collected from 40 participants enrolled in the Phase II Butantan-DV clinical trial (NCT01696422) before and after (days 6, 12, 15 and 22) vaccination. We observed a peak in the number of circulating plasmablast at day 15 after vaccination in both the DENV naïve and the DENV-exposed vaccinees. DENV-exposed vaccinees experienced a significantly higher plasmablast expansion. In the DENV-naïve vaccinees, plasmablasts persisted for approximately three weeks longer than among DENV-exposed volunteers. Our findings indicate that the Butantan-DV can induce plasmablast responses in both DENV-naïve and DENV-exposed individuals and demonstrate the influence of pre-existing DENV immunity on Butantan DV-induced B-cell responses.